A comparative study of Ocean Literacy features in the science curricula of China and the United States: promoting oceanic power through formal education - Lu, Yihua; Cheng, Jian; Wang, Kun; Zhang, Mingcan; Chen, Shi (Frontiers in Education, 2025)
IntroductionOcean Literacy (OL), as a core element in enhancing citizens’ Ocean Awareness, has gained wide attention in the field of education. However, existing studies indicate that the integration of OL into formal education remains insufficient. To address this gap, this study conducts a comparative analysis of the extent to which OL is incorporated into the science curriculum standards of China and the United States, and further examines the underlying ocean education philosophies in both countries.MethodsThis study employed content analysis and Epistemic Network Analysis (ENA). Using content analysis, we examined the science curriculum standards of China and the United States with respect to: (1) the scope of coverage — the presence of the seven principles of the Ocean Literacy Framework (OLF) in the documents; (2) the quantity distribution — the occurrence frequency of each principle; and (3) the grading ranks — the forms in which the principles are represented. Using ENA, we treated the OL principles as network nodes and compared the structural differences between the two countries’ OL epistemic networks based on node size and inter-node relations, thereby illuminating each country’s underlying ocean education philosophy.Results and DiscussionThe results showed that the science curriculum of both countries covered the seven principles, yet exhibited notable similarities and differences across different educational stages and subject areas, thereby revealing the respective strengths and weaknesses in fostering OL. In addition, the ENA results highlighted distinctive emphases in the two countries’ ocean education philosophies: China stresses the “human–sea relationship,” while the United States focuses on an “interdisciplinary perspective to explain the principles of ocean system and ocean science.” Finally, the ENA results also pointed out specific shortcomings in the connections among OL principles within the science curriculum standards of both countries. Based on these findings, this study offers concrete recommendations for policy-makers, curriculum developers, and practitioners in ocean science research and education to further promote the integration of OL into formal curricula.